EFFECT OF SUBCUTANEOUS ZERANOL IMPLANTS ON MEAT QUALITY OF AWASSI LAMBS AND CROSS-BRED KHALKHALI AND ABADEH GOAT KIDS - Al-doski, S. H.; Kak, H. F.; Khurshid, J. S.; Vriesekoop, F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This experiment was conducted to evaluate the effects zeranol implant on meat quality of Awassi lambs and cross-bred Khalkhali and Abadeh goat kids. Ten ram lambs (33.7 ± 0.5 kg and 4-month-old) and ten male goat kids (18.8 ± 0.7 kg and 4-month-old) were randomly assigned into two treatments (5 each treatment); C (control, 0 mg zeranol) and Z (24 mg zeranol implant) for each species. After 43 days experimental period. The animals were slaughtered, left for 24 hr post-mortem period and Biceps femoris muscle of each species were separated for measuring the proximal composition, TBARS values, cooking loss, drip loss and free fatty acids concentrations. Zeranol implants had significant (P<0.05) effect on dry matter, but did not have any effect on all other meat characteristics. However, dry mater was significantly higher for zeranol-implanted group as compared with control one. Moreover, significant effect of animal species was found for cooking loss, being highest in goat meat than ram lamb meat. Similarly, significant effect of animal species was noticed on TBARS values being highest in ram lamb meat. An obvious increase (P<0.005) in drip loss and TBARS values were observed for meat of both zeranol-implanted and non-implanted groups with storage period. It can be concluded that zeranol implant did not have any effect on meat quality for both ram lambs and male goat kids’ meat.